Livros didáticos de ensino religioso: Análise da construção da polêmica no discurso da mídia - Garrido, Bruno Sampaio [UNESP] (Universidade Estadual de Maringa, 2012)
This text aims to identify the discursive relations and the mechanisms used by sources - discourses gathered at press and specialized sites - in composing of viewpoints presented about the religious education textbooks and, a result of that, of controversial relationship built thereafter. The theoretical foundation of this work rests largely on the concepts of global semantics and constitutive intermisunderstanding (MAINGUENEAU, 1997, 2008) and discursive heterogeneity (AUTHIER-REVUZ, 1990, 1998). The research corpus consisted of four texts, three of which were published in 2010 and another in 2011, two reports and two opinion articles about the subject. From our analysis, we could see the construction of a controversial relationship between a discursive formation that challenges the teaching of religion in Brazilian public education, on the grounds that benefit the Christian faith and, moreover, one that supports the continuation of this practice and consider it important for the formation of the student and also as a promoter of diversity and equality.
Textbooks of religious education: Polemics composing analysis at media discourse
Keywords: Discursive relations; Global semantics; Journalism; Religious education; Teaching material